A Study To Evaluate The Effectiveness Of Humorous Videos On Stress Among Old Age People In Selected Old Age Home At Madurai - Kumar, R.Ahilan Vinoth; Nappinnai, Nappinnai; Vijayalakshmi, Vijayalakshmi (Journal of Neonatal Surgery, 2025)
N